MODEL HIDROLOGI DAS ITN I - Kustamar Kustamar (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2009)
Physical spatial factors of watershed such as topography, soil types and land use show a prominentcontribution in the distributed water shed modeling. One of the difficulties encountered is the change oftopographical information in map form into data that can be read by model program. In the process ofanalyses, physical spatial factor of water shed is divided into grid system consisting of rectangular cellsgroups. In each cell, surface run off discharge ,including its direction, is determined based on the depths byapplying a one dimension unsteady flow concept whereas direction is determined by using information onfour points of the cells. Water depth of the surface run off can be calculated by using both a vertical watermovement model and land use area condition. The model has been tested using the available data of Lesti(East Java) watershed. From calibration and verification processes, this so called Hydrological Model ofITN 1 has been successfully applied with very good reliability.